A visual programming language for soccer - Belguinha, António (2014)
The use of Information Technologies (IT) in high competition sports is an instrument often used. However, the majority of the performers, including technical teams, do not have skills to program those IT tools to their needs. In this paper we present the low level implementation of a visual programming language (VPL) that allows the user without programming expertise to produce relatively complex programs by drawing them on a web application. The VPL tool application is illustrated by applying it to detect programmed situations from a soccer game, using previously obtained tracking data. The tool can be applied to other collective ball sports.